PLATELET-RICH PLASMA (PRP) IN MODERN DERMATOLOGY AND AESTHETIC MEDICINE: BIOLOGICAL MECHANISMS, CLINICAL APPLICATIONS, AND FUTURE DIRECTIONS - Karolina Zygoń-Komendarczyk; Katarzyna Oberska; Sandra Olewińska; Pola Sitek; Dariusz Szołtys; Aleksandra Lisowska; Michalina Adamczyk; Tola Kotkiewicz; Oliwia Jerzyńska; Yelyzaveta Petrenko (International Journal of Innovative Technologies in Social Science, 2026)
Platelet-rich plasma (PRP) is an autologous blood-derived biologic increasingly used in dermatology and aesthetic medicine due to its regenerative and immunomodulatory effects. By providing a concentrated source of platelets and their mediators, PRP has the potential to enhance angiogenesis, promote collagen remodeling, and facilitate tissue repair. These properties support its application in various areas, including hair loss treatment, scar revision, chronic wound management, and minimally invasive rejuvenation procedures. This narrative review aims to summarize the current human clinical evidence regarding PRP, focusing on its biological mechanisms, preparation methods, clinical outcomes, safety profile, and future directions. A structured search was performed in PubMed, Scopus, and Web of Science for English-language studies involving human subjects published from 2010 to 2025. The search prioritized randomized controlled trials, comparative studies, and recent systematic reviews or meta-analyses. The existing evidence most strongly supports the effectiveness of PRP in treating androgenetic alopecia and as a complementary treatment for device-based acne scar therapies, such as microneedling or fractional lasers. However, significant variability in preparation techniques—such as single versus double centrifugation, platelet dosage, leukocyte content, activation methods, and treatment schedules—poses challenges for comparability and reproducibility of results. Overall, PRP is generally well tolerated, with adverse effects typically being mild and temporary. For future advancements, it will be essential to establish standardized frameworks for characterizing PRP, enhance the reporting of its composition, and conduct rigorous long-term studies that utilize technology for improved outcome assessment.